KESEHATAN DAN KESEJAHTERAAN DI SEKOLAH TERUTAMA TERHADAP GEN Z - Dini; Nengsih; Rangga Aldiansyah; Paujan Adima Rujiana (PT. Hasba Edukasi Mandiri, 2026)
“Health and Well-Being in Schools” is a Community Service activity aimed at increasing the knowledge and awareness of vocational high school (SMK) students, especially Generation Z, regarding the importance of health and well-being in the school environment. This activity was conducted at SMKN 7 Kota Serang and was motivated by the importance of maintaining health and well-being as basic needs that influence students’ quality of life and learning processes. The methods used included an initial survey to identify problems, the preparation of research instruments in the form of post-test questionnaires, and the preparation of educational materials. The activity was carried out through counseling and question-and-answer methods to provide understanding regarding public health, well-being, and the implementation of healthy lifestyles in the school environment. This activity is expected to encourage the creation of a school environment that supports healthy lifestyle behaviors, such as handwashing with soap, and provide practical recommendations for maintaining student health and well-being.